Method for preparing gel electrolyte by inducing normal-temperature in-situ polymerization of high-pressure-resistant monomer through multifunctional additive
By induced high-pressure resistant monomer polymerization with Lewis acid-based multifunctional additives at room temperature, the problems of uneven distribution and side reactions during the heating polymerization process are solved, and the preparation of high-specific energy solid-state lithium batteries is realized, which improves the safety of the batteries. and specific energy density.
Patent Information
- Application Number
- CN202411488065.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-24
AI Technical Summary
The existing high-pressure resistant monomers have problems of uneven distribution and increased side reactions during the heating polymerization process, which limits the realization of high-specific energy solid-state batteries, and there are safety hazards in liquid electrolytes.
By introducing Lewis acid-based multifunctional additives and performing in-situ polymerization at room temperature, gel electrolytes that can match high-voltage, high-capacity positive electrodes and high-capacity negative electrodes are prepared, reducing energy consumption and improving the electrochemical window.
Effective polymerization at room temperature is achieved, uneven distribution and side reactions are avoided, electrochemical stability and safety are improved, high-voltage and high-capacity electrodes are matched, and specific energy density of lithium batteries is improved.
Smart Images

Figure CN119241750A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new energy materials and devices, and specifically relates to a method of inducing in-situ polymerization of high-voltage resistant monomers at room temperature by multifunctional additives to prepare a gel electrolyte that can match high-voltage, high-capacity positive electrodes and high-capacity negative electrodes, which is used to assemble high-energy-density solid-state lithium batteries. Background Art
[0002] As an important energy storage method and power support for the operation of the new energy industry, batteries are of great significance to the true realization of the country's dual-carbon strategic goals. At present, the energy density of commercial lithium iron phosphate / graphite battery systems has reached more than 300Wh / kg, which is close to the theoretical limit and is far from meeting the growing mileage requirements, so it is urgent to improve the energy density of batteries. At the same time, most of the liquid electrolytes used in existing batteries have intrinsic flammability and leakage risks, posing safety hazards. Therefore, the development of high-safety, high-energy-density lithium batteries with solid-state and quasi-solid-state electrolytes as the core is an important means to upgrade the battery system.
[0003] Gel electrolytes composed of polymer matrix and liquid plasticizer have been developed as a quasi-solid electrolyte. They combine the advantages of all-solid electrolytes and liquid electrolytes and are the most promising solid electrolytes at this stage. In-situ polymerization can make the solid electrolyte have good contact with both the positive and negative electrodes and form ion channels to match the high-load positive electrode. It is a very promising method for preparing gel electrolytes. However, in order to achieve the goal of high-energy solid-state batteries, the electrolyte needs to have a wide electrochemical window to match the high-voltage and high-capacity positive electrode materials, which places extremely high demands on the polymerized monomers. The most common polymerized monomers that can withstand high voltages have ester groups and carbon-carbon double bond conjugated structures, and polymerization needs to be initiated at above 50°C. However, the precursor solution is often unevenly heated and easily heated and flows, resulting in uneven distribution of the gel electrolyte after polymerization; at the same time, the side reactions between the positive and negative electrodes and the electrolyte are greatly increased during heating, which limits the application of common high-voltage resistant monomers in actual production.
[0004] Therefore, the present invention, through the addition of Lewis acid-based multifunctional additives, improves the electrochemical window to match the high-voltage positive electrode and protects the high-capacity negative electrode, while reducing energy consumption and completing in-situ polymerization at room temperature. It is a preparation method of gel electrolytes with great potential for application in high-energy-density solid-state batteries. Summary of the invention
[0005] In view of the problems existing in the prior art in the heating polymerization process of high-voltage resistant monomers and the design needs of high-energy-density solid-state batteries, the present invention provides a method for preparing a gel electrolyte that can match a high-voltage, high-capacity positive electrode and a high-capacity negative electrode to assemble a high-energy-density solid-state lithium battery by inducing in-situ polymerization of high-voltage resistant monomers at room temperature through a multifunctional additive.
[0006] The technical solution for implementing the present invention is as follows:
[0007] The present invention provides a method for preparing a gel electrolyte that can match a high-voltage, high-capacity positive electrode and a high-capacity negative electrode by inducing a high-voltage resistant monomer to perform in-situ polymerization at room temperature through a multifunctional additive, comprising the following steps:
[0008] (1) mixing and dissolving a polymerization monomer, a plasticizer, and a multifunctional additive to form a homogeneous precursor solution 1;
[0009] (2) mixing and dissolving the initiator and the plasticizer to form a homogeneous precursor solution 2;
[0010] (3) mixing precursor solutions 1 and 2 to form a homogeneous precursor solution 3;
[0011] (4) Inject the precursor solution 3 into the battery casing and allow it to stand at room temperature (20°C-35°C) for in-situ polymerization to obtain a gel electrolyte solid-state battery, wherein the battery uses a high-voltage, high-capacity inorganic material, including but not limited to any one of lithium-rich manganese-based, nickel-cobalt-manganese-based, and lithium cobalt oxide as the positive electrode, and any one of high-capacity lithium metal, lithium-based alloy, and silicon-carbon as the negative electrode.
[0012] Preferably, the amount is as follows by mass:
[0013] Polymerization monomer: 1-30 parts;
[0014] Plasticizer: 60-98.5 parts;
[0015] Multifunctional additives: 0.1-10 parts;
[0016] Initiator: 0.1-3 parts.
[0017] Preferably, the polymerizable monomer has an ester group and a carbon-carbon double bond conjugated structure, including but not limited to pentaerythritol tetraacrylate (PETEA) and ethoxylated trimethylolpropane triacrylate (ETPTA).
[0018] Preferably, the plasticizer is a liquid electrolyte that can withstand high voltage, and the formula includes but is not limited to: lithium difluorooxalatoborate (LiDFOB) added with fluoroethylene carbonate (FEC) / methyl trifluoroethyl carbonate (FEMC).
[0019] Preferably, the multifunctional additive is Lewis acid, which has the functions of forming a complex with the polymerizable monomer, improving polymerization activity, increasing the electrochemical stability window, protecting the negative electrode, etc., including but not limited to tri(pentafluorophenyl)borane (TPFPB).
[0020] Preferably, the initiator is an azo thermal initiator, including but not limited to azobisisobutyronitrile (AIBN).
[0021] Preferably, the battery housing includes but is not limited to a commercial XR2032 assembled battery, and the amount of the electrolyte precursor solution is 10 μL-100 μL.
[0022] Preferably, the battery housing includes but is not limited to one of a soft-pack battery, a square battery, a cylindrical battery, a laminated battery, and a wound battery.
[0023] Preferably, the room temperature standing temperature is 20°C-35°C, and the standing time is 3h-48h.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) The Lewis acid-based multifunctional additive developed by the present invention has the functions of reducing the polymerization temperature of high-voltage resistant polymerization monomers, improving the electrochemical window of the system, and protecting the negative electrode;
[0026] (2) The present invention initiates the polymerization of high-voltage resistant monomers having an ester group and a carbon-carbon double bond conjugated structure at room temperature, which greatly improves the problems encountered under common heating polymerization conditions, including (i) uneven heating causing the precursor solution to flow and be unable to be evenly distributed; (ii) uneven heating causing violent polymerization; and (iii) volatilization of liquid components inside the battery when heated. It also has the advantages of reducing high-temperature side reactions and lowering energy consumption.
[0027] (3) The gel electrolyte prepared by the present invention can match a high-voltage, high-capacity positive electrode and a high-capacity negative electrode, thereby realizing a high-energy-density solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a comparison of the polymerization conditions at room temperature (20°C-35°C) without addition (Comparative Example 1) and with addition of multifunctional additive (TPFPB) (Example 1) as a function of standing time;
[0029] Figure 2 It is a comparison of the uniformity of distribution of gel electrolyte after polymerization at room temperature (TPFPB) (Example 1) and heating polymerization (60°C) (Comparative Example 1);
[0030] Figure 3 It is a comparison diagram of linear sweep voltammetry (LSV) curves of room temperature polymerization (TPFPB) (Example 2) and heated polymerization (60° C.) (Comparative Example 2);
[0031] Figure 4 It is a comparison chart of the Li—Cu coulombic efficiency of room temperature polymerization (TPFPB) (Example 3) and heated polymerization (60° C.) (Comparative Example 3).
[0032] Figure 5It is the charge and discharge curve of room temperature polymerization (TPFPB) (Example 4) with lithium-rich manganese as the positive electrode and lithium metal as the negative electrode half-cell, full battery first cycle (0.1C), and second cycle (0.1C);
[0033] Figure 6 It is a comparison chart of the capacity retention rate-cycle number of full batteries (0.2C) with lithium-rich manganese as the positive electrode and lithium metal as the negative electrode by room temperature polymerization (TPFPB) (Example 4) and heated polymerization (60°C) (Comparative Example 4). DETAILED DESCRIPTION
[0034] The present invention will be further explained below through the accompanying drawings and specific examples. The following examples are only used as an illustration and should not be understood as limiting the scope of the present invention. The protection scope of the present invention is not limited to the following embodiments.
[0035] Example 1
[0036] A method for preparing a high-voltage, high-capacity positive electrode and a high-capacity negative electrode gel electrolyte that can match high voltage and high-capacity positive electrode and high-capacity negative electrode by inducing a high-voltage resistant monomer to undergo in-situ polymerization at room temperature through a multifunctional additive, the steps being as follows:
[0037] (1) 15 mg of high pressure resistant monomer PETEA, 5 mg of multifunctional additive TPFPB, and 661 μL of plasticizer were mixed and dissolved to form a homogeneous precursor solution 1;
[0038] (2) 10 mg of initiator AIBN and 200 μL of plasticizer were mixed and dissolved to form a homogeneous precursor solution 2;
[0039] (3) Use a pipette to take out 20 μL from the precursor solution 2 and add it to the precursor solution 1 to form a homogeneous precursor solution 3. The injection tool is preferably a pipette with a range of 100 μL;
[0040] (4) leaving the precursor solution 3 in the vial at room temperature (20°C-35°C) to stand until the in-situ polymerization is completed, and obtaining an optical image of the gel electrolyte;
[0041] (5) The precursor solution 3 that was not left to stand in Example 1 was assembled into an SS-SS half-cell. The SS-SS half-cell was assembled with stainless steel gaskets (SS) for both the positive and negative electrodes to observe the internal polymerization of the battery. The amount of precursor solution 3 was 50 μL. The battery was assembled using a pressure of 0.85 tons and then left to stand at room temperature (20°C-35°C) for 24 hours to complete the in-situ polymerization. The diaphragm was Celgard2500, and the injection tool was preferably a pipette with a range of 100 μL.
[0042] Figure 1The polymerization of the precursor solution 3 in the vial of Example 1 and Comparative Example 1 after standing at room temperature for 10 hours is shown. The addition of the multifunctional additive can obviously induce the high-pressure resistant monomer to complete polymerization at room temperature. Figure 2 The SS-SS half-cell in Example 1 was kept at room temperature for 24 hours, and the SS-SS half-cell in Comparative Example 1 was kept at 60°C for 6 hours before the battery was disassembled to obtain the separator. Example 1 avoids the problem of uneven distribution of the gel electrolyte caused by uneven heating, volatilization of liquid components, etc.
[0043] Example 2
[0044] The precursor solution 3 that was not left to stand in Example 1 was assembled into an SS-Li half-cell, and the SS-Li half-cell was assembled with a stainless steel gasket (SS) as the positive electrode and a Li sheet with a diameter of 14 mm and a thickness of 450 μm as the negative electrode to test the electrochemical stability window. The amount of precursor solution 3 was 50 μL, and the battery was assembled using 0.85 tons of pressure and then stood at room temperature (20°C-35°C) for 24 hours to complete the in-situ polymerization. The diaphragm was Celgard 2500, and the injection tool was preferably a pipette with a range of 100 μL.
[0045] SS-Li half-cell for electrochemical window test, assembled at 0.2 mV s -1 The LSV curve was obtained by testing with an electrochemical workstation at a scan rate of 2.5-8 V. Figure 3 2 are the LSV curves of Example 2 and Comparative Example 2. The electrochemical window of Example 2 is greater than 6V, which is significantly higher than that of Comparative Example 2.
[0046] Example 3
[0047] The precursor solution 3 that was not left to stand in Example 1 was assembled into a Li-Cu half-cell, and the coulombic efficiency was tested by assembling a Li-Cu half-cell with a positive electrode being a copper foil (Cu) and a negative electrode being a Li sheet with a diameter of 14 mm and a thickness of 450 μm. The amount of precursor solution 3 was 50 μL, and the battery was assembled using a 0.85-ton pressure and then left to stand at room temperature (20°C-35°C) for 24 hours to complete the in-situ polymerization. The diaphragm was Celgard 2500, and the injection tool was preferably a pipette with a range of 100 μL.
[0048] Li-Cu half-cell for Coulombic efficiency test, assembled at 0.5 mA cm -2 , 0.5mAh cm -2 Carry out the cycle. Figure 4 The Li-Cu coulombic efficiency of Example 3 and Comparative Example 3 is 96.50%, which is significantly better than Comparative Example 3 (93.71%).
[0049] Example 4
[0050] The battery was assembled using the precursor solution 3 that was not left to stand in Example 1. The battery shell was a commercial XR2032 assembled battery. The positive electrode was a lithium-rich manganese-based material, the negative electrode was lithium metal, and the positive electrode diameter of the full battery was 10 mm and the loading was 15 mg cm -2 , the negative electrode is a Li sheet with a diameter of 10mm and a thickness of 50μm, the amount of precursor solution 3 added is 15-20μL, the battery is assembled using a 0.85-ton pressure and left to stand at room temperature (20℃-35℃) for 24h until the in-situ polymerization is completed, the diaphragm is Celgard 2500, and the injection tool is preferably a pipette with a range of 100μL;
[0051] The assembled full battery was activated at 0.1C for 3 cycles and then charged and discharged at 0.2C, 1C = 250mAh g -1 . Figure 5 The first and second cycle charge-discharge curves of Example 4. The first cycle discharge capacity exceeds 250 mAh g -1 , reaching 269.6mAh g -1 , with the feasibility of high specific energy. Figure 6 The capacity retention rate changes during the full battery charge and discharge cycle of Example 4 and Comparative Example 4. The cycle performance of Example 4 is significantly better than that of Comparative Example 4.
[0052] Comparative Example 1
[0053] A method for preparing a high-voltage, high-capacity positive electrode and a high-capacity negative electrode gel electrolyte by heating in-situ polymerization, the steps are as follows:
[0054] (1) 15 mg of high pressure resistant monomer PETEA and 664 μL of plasticizer were mixed and dissolved to form a homogeneous precursor solution 1;
[0055] (2) 10 mg of initiator AIBN and 200 μL of plasticizer were mixed and dissolved to form a homogeneous precursor solution 2;
[0056] (3) Use a pipette to take out 20 μL from the precursor solution 2 and add it to the precursor solution 1 to form a homogeneous precursor solution 3. The injection tool is preferably a pipette with a range of 100 μL;
[0057] (4) leaving the precursor solution 3 in the vial at room temperature (20° C.-35° C.) to obtain an optical image;
[0058] (5) The precursor solution 3 in comparative example 1 that was not left to stand was assembled into an SS-SS half-cell, and the SS-SS half-cell was assembled with stainless steel gaskets (SS) for both the positive and negative electrodes to observe the internal polymerization of the battery. The amount of precursor solution 3 was 50 μL, and the battery was assembled using a 0.85-ton pressure and then moved to an oven, heated (60°C) for 6 hours until the in-situ polymerization was completed. The diaphragm was Celgard 2500, and the injection tool was preferably a pipette with a range of 100 μL.
[0059] Comparative Example 2
[0060] The precursor solution 3 that was not left to stand in comparative example 1 was assembled into an SS-Li half-cell, and the electrochemical stability window was tested by assembling the SS-Li half-cell with a stainless steel gasket (SS) as the positive electrode and a Li sheet with a diameter of 14 mm and a thickness of 450 μm as the negative electrode. The amount of precursor solution 3 was 50 μL, and the battery was assembled using a 0.85-ton pressure and then moved to an oven, heated (60°C) for 6 hours to complete the in-situ polymerization. The diaphragm was Celgard 2500, and the injection tool was preferably a pipette with a range of 100 μL.
[0061] SS-Li half-cell for electrochemical window test, assembled at 0.2 mV s -1 The LSV curve was obtained by testing with an electrochemical workstation at a scan rate and in the range of 2.5-6 V. Figure 3 2 are the LSV curves of Example 2 and Comparative Example 2. The electrochemical window of Comparative Example 1 is <5V, which is significantly lower than that of Example 2.
[0062] Comparative Example 3
[0063] The precursor solution 3 that was not left to stand in comparative example 1 was assembled into a Li-Cu half-cell, and the coulombic efficiency was tested by assembling a Li-Cu half-cell with a copper foil (Cu) as the positive electrode and a Li sheet with a diameter of 14 mm and a thickness of 450 μm as the negative electrode. The amount of precursor solution 3 was 50 μL, and the battery was assembled using a 0.85-ton pressure and then moved to an oven, heated (60°C) for 6 hours to complete the in-situ polymerization. The diaphragm was Celgard 2500, and the injection tool was preferably a pipette with a range of 100 μL.
[0064] Li-Cu half-cell for Coulombic efficiency test, assembled at 0.5 mA cm -2 , 0.5mAh cm -2 Carry out the cycle. Figure 4 The Li-Cu coulombic efficiency of Example 3 and Comparative Example 3 is 93.71%, which is significantly lower than that of Example 3 (96.50%).
[0065] Comparative Example 4
[0066] The battery was assembled using the precursor solution 3 that was not left to stand in comparative example 1. The battery shell was a commercial XR2032 assembled battery. The positive electrode was a lithium-rich manganese-based material, the negative electrode was lithium metal, and the positive electrode diameter of the full battery was 10 mm and the loading was >15 mg cm -2 , the negative electrode is a Li sheet with a diameter of 10 mm and a thickness of 50 μm, the amount of precursor solution 3 added is 15-20 μL, the battery is assembled using a 0.85 ton pressure and then moved to an oven, heated (60°C) for 6 hours until the in-situ polymerization is completed, the diaphragm is Celgard 2500, and the injection tool is preferably a pipette with a range of 100 μL;
[0067] The assembled full battery was activated at 0.1C for 3 cycles and then charged and discharged at 0.2C, 1C = 250mAh g -1 . Figure 6 The capacity retention rate changes during the full battery charge and discharge cycle of Example 4 and Comparative Example 4. The cycle performance of Comparative Example 4 is significantly weaker than that of Example 4.
[0068] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, several improvements and optimizations can be made, including improvements and optimizations of high-pressure resistant polymerization monomers, plasticizers, Lewis acid-based multifunctional additives, and initiators having ester groups and carbon-carbon double bond conjugated structures. These improvements and optimizations should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a gel electrolyte by inducing in-situ polymerization of a high-voltage resistant monomer at room temperature using a multifunctional additive, characterized in that: The steps include: (1) mixing and dissolving a polymerization monomer, a plasticizer, and a multifunctional additive to form a homogeneous precursor solution 1; (2) mixing and dissolving the initiator and the plasticizer to form a homogeneous precursor solution 2; (3) mixing precursor solutions 1 and 2 to form a homogeneous precursor solution 3; (4) Inject the precursor solution 3 into the battery casing, and place it at room temperature of 20°C-35°C for in-situ polymerization to obtain a gel electrolyte solid-state battery, wherein the battery uses a high-voltage, high-capacity inorganic material as the positive electrode, including but not limited to any one of lithium-rich manganese-based, nickel-cobalt-manganese-based, and lithium cobalt oxide materials, and any one of high-capacity lithium metal, lithium-based alloy, and silicon-carbon as the negative electrode.
2. The method for preparing gel electrolyte by inducing in-situ polymerization of high-voltage resistant monomers at room temperature by a multifunctional additive according to claim 1, characterized in that: Described consumption is calculated as follows by mass parts: Polymerization monomer: 1-30 parts; Plasticizer: 60-98.5 parts; Multifunctional additives: 0.1-10 parts; Initiator: 0.1-3 parts.
3. The method for preparing gel electrolyte by inducing in-situ polymerization of high-voltage resistant monomers at room temperature by a multifunctional additive according to claim 1 or 2, characterized in that: The polymerizable monomer has an ester group and a carbon-carbon double bond conjugated structure, including but not limited to isopentaerythritol tetraacrylate PETEA and ethoxylated trimethylolpropane triacrylate ETPTA.
4. The method for preparing gel electrolyte by inducing in-situ polymerization of high-voltage resistant monomers at room temperature by a multifunctional additive according to claim 1 or 2, characterized in that: The plasticizer is a liquid electrolyte that can withstand high voltage. The formula includes but is not limited to: lithium difluorooxalate borate LiDFOB added with fluoroethylene carbonate FEC / methyl trifluoroethyl carbonate FEMC.
5. The method for preparing gel electrolyte by inducing in-situ polymerization of high-voltage resistant monomers at room temperature by a multifunctional additive according to claim 1 or 2, characterized in that: The multifunctional additive is a Lewis acid having the ability to form a complex with a polymerizable monomer, including but not limited to tri(pentafluorophenyl)borane TPFPB.
6. The method for preparing gel electrolyte by inducing in-situ polymerization of high-voltage resistant monomers at room temperature by using a multifunctional additive according to claim 1 or 2, characterized in that: The initiator is an azo thermal initiator, including but not limited to azobisisobutyronitrile AIBN.
7. The method for preparing gel electrolyte by inducing in-situ polymerization of high-voltage resistant monomers at room temperature by a multifunctional additive according to claim 1, characterized in that: The battery shell includes but is not limited to a commercial XR2032 assembled battery, and the amount of the electrolyte precursor solution 3 used is 10 μL-100 μL.
8. The method for preparing gel electrolyte by inducing in-situ polymerization of high-voltage resistant monomers at room temperature by a multifunctional additive according to claim 1, characterized in that: The battery housing includes but is not limited to one of a soft-pack battery, a square battery, a cylindrical battery, a laminated battery, and a wound battery.
9. The method for preparing gel electrolyte by inducing in-situ polymerization of high-voltage resistant monomers at room temperature by a multifunctional additive according to claim 1, characterized in that: The room temperature standing temperature is 20℃-35℃, and the standing time is 3h-48h.
Citation Information
Patent Citations
Gel electrolyte as well as preparation method and application thereof
CN113224370A
High-performance gel polymer electrolyte as well as preparation method and application thereof
CN114478913A
Single-ion gel polymer electrolyte as well as preparation and application thereof
CN115117442A
Gel electrolyte for silicon-carbon material, preparation method of gel electrolyte and battery
CN116284523A
Solid polymer electrolyte with local high-concentration structure, lithium battery and method
CN117423898A
Cited By
Hydrogel-based high-voltage aqueous lithium ion fiber battery and preparation method thereof
CN121839915A
